Herba Reudeuep With Modification of Heating In Virgin Cocanut Oil - Wahyuzan Wahyuzan; Lukmanul Hakim; Rahmat Afrizal; Asmeri Lamona; Khairuni Khairuni; Liya Fitriyana (Universitas Serambi Mekkah, 2020)
Traditional medicine in Indonesia has been known by the public before formal health services using modern medicine. Indonesia has many type of herbal plants which have medicinal properties including dadap (Erythrina orientalis). This study aims to utilized dadap herbal liniment by modifying heating in Vigin Cocanut Oil. The study conducted in the laboratory of Agricultural Product Processing using a Factorial Completely Randomized Design (CRD). The first factor is the addition of 250 ml (M1), 375 ml (m2), and 400 ml (M3) Virgin Cocanut Oil treatment. The second factor is the heating tim of 5 minutes (L1), 10 minutes (L2), and 15 minutes (L3). Observation variable consisted of yield, Specific gravity, and organoleptic test of aroma and colored. The result showed an average yield of 87.70-91.88%. The highest yield was found in the treatment of adding 400 ml Virgin Cocanut Oil and 15 minutes of heating time. The highest type of weight was found in the treatment of addition of 325 ml Virgin Cocanut Oil and 5 minutes heating time. Based on the organoleptic scent test, the everage penalist gives a like answer. Organoleptic colors of reudeuep herbal products is according to SNI number 06-23-2006.